Effect of GO agglomeration on the mechanical properties of graphene oxide and nylon 66 composites and micromechanical analysis. Issue 11 (26th August 2022) - Chen, Qi; Guo, Zhangxin; Cheng, Feng; Chai, Gin Boay; Li, Yongcun; Luan, Yunbo; Liang, Jianguo
Abstract: Nanoparticles are prone to aggregation in the matrix under the action of surface energy, chemical bonding, electrostatic attraction, and van der Waals forces. Based on the molecular dynamics method, the tensile properties of graphene oxide (GO)‐reinforced nylon 66 composites were simulated and calculated, and the stress–strain curves, atomic stress clouds, and changes in the number of hydrogen bonds were obtained for the composites under tensile loading, and the effects of GO agglomeration on the mechanical properties of GO/PA66 composites were analyzed. When the GO mass fraction accounted for 90.3%, 80.5%, and 70.6% of the model, respectively, the mechanical properties of the composites decreased by 15.4%, 4.5%, and 4.2%, respectively. Because GO agglomeration in the composites made it difficult to bond effectively between GO and PA66, the number of hydrogen bonds and the type of hydrogen bonds within the model, varied with the degree of aggregation. The changes in the number of hydrogen bonds and the type of hydrogen bonds during uniaxial stretching were simulated by molecular dynamics. The number of hydrogen bonds and the type of hydrogen bonds directly affect the mechanical properties of the composites. It can be seen from the atomic stress cloud diagram that the aggregation of GO makes the mechanical properties of GO fail to exert effectively. The main stress is on the C atoms in the outermost layer of GO, while the stress on the inner layer C atoms is relatively small. As the degree of GO agglomeration decreases, the stress on each C atom of GO lamellae tends to be uniform, which effectively brings into play the excellent mechanical properties of GO and improves the mechanical properties of the composite. Abstract : GO/PA66 model.